2019
DOI: 10.1172/jci.insight.131610
|View full text |Cite
|
Sign up to set email alerts
|

Using a barcoded AAV capsid library to select for clinically relevant gene therapy vectors

Abstract: Conflict of interest: KP and MAK are named on patent applications for AAV variants used in this paper. MAK has equity interests in LogicBio Therapeutics. MG has equity interests in Yecuris Corp., Ambys Medicines, and LogicBio Therapeutics. MH owns stock in Encellin and Viacyte Inc., receives research support from Eli Lily, and holds roles as consultant and member of the scientific advisory board for Semma Therapeutics and Encellin.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 77 publications
2
75
1
Order By: Relevance
“…1A). 10 This 18 AAV capsid pool was used for initial studies as it has a low complexity and thus represents a powerful tool to optimize AAV library screens. The starting proportion of each of the barcodes is represented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1A). 10 This 18 AAV capsid pool was used for initial studies as it has a low complexity and thus represents a powerful tool to optimize AAV library screens. The starting proportion of each of the barcodes is represented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The method for generation of a pool consisting of a defined number of parental capsid AAVs is described in Ref. 10 Briefly, capsids from 18 AAV serotypes (AAV1, AAV2, AAV3B, AAV4, AAV5, AAV6, AAV8, AAV9, AAV12, AAVporcine1, AAVporcine2, AAVbovine, AAVgoat1, AAVmouse1, AAVavian, AAVrh10, AAV-DJ, and AAV-LK03) were cloned into the BC library vector. Each AAV capsid contained a unique barcode sequence.…”
Section: Generation Of the 18 Aav Capsid Poolmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that AAV neutralizing antibodies do not have as much of an effect when inoculations are administered intramuscularly (Greig et al, 2016), which makes skeletal muscle tissue an easier target compared to the liver. Another approach could be through the use of synthetic capsids (Büning and Srivastava, 2019;Pekrun et al, 2019). Both rational design and directed evolution studies are being employed to generate synthetic capsids that improve AAV transduction to specific tissues and avoid the pre-existing neutralizing antibody responses.…”
Section: Current Limitations When Using Raav Vectorsmentioning
confidence: 99%